You see Froot, you think fruit: examining the effectiveness of pseudohomophone priming. (8th May 2017) - Baxter, Stacey; Ilicic, Jasmina; Kulczynski, Alicia
Abstract : Purpose: This paper aims to introduce pseudohomophone phonological priming effects (non-words that sound like real words with a single semantic representation, such as Whyte primes white) on consumers' product attribute and benefit-based judgments. Design/methodology/approach: Four studies were conducted. Study 1 examines whether pseudohomophone brand names (e.g. Whyte) prime associative meaning (i.e. the perception of light bread; target: white). Study 2 investigates the pseudohomophone priming process. In Study 3, the authors examine the influence of brand knowledge of pseudohomophone priming effects. Findings: The findings indicate that pseudohomophone brand names prime associative meaning, due to retrieval of phonology (sound) of the word during processing. Pseudohomophone priming effects for a semantically (meaningful) incongruent brand name manifest only when consumers do not have knowledge of the brand, with cognitive capacity constraints rendering consumers with strong brand knowledge unable to mitigate the pseudohomophone priming effect. Research limitations/implications: This research has implications for brand managers considering the creation of a name for a new brand that connotes product attributes and benefits. However, this research is limited, as it only examines pseudohomophone brand names with a single semantic representation. Originality/value: This research shows that sounds activated by pseudohomophones in brand names can influence product judgments. This research also identifies limitations of the applicability of pseudohomophone brand names by identifying a condition under which priming effects are attenuated.